Sphingosylphosphorylcholine Antagonizes Proton-Sensing Ovarian Cancer G-Protein-Coupled Receptor 1 (OGR1)-Mediated Inositol Phosphate Production and cAMP Accumulation - Chihiro Mogi; Hideaki Tomura; Masayuki Tobo; Ju-Qiang Wang; Alatangaole Damirin; Junko Kon; Mayumi Komachi; Kinji Hashimoto; Koichi Sato; Fumikazu Okajima (Elsevier, 2005)
Ovarian cancer G-protein-coupled receptor 1 (OGR1), previously proposed as a receptor for sphingosylphosphorylcholine (SPC), has recently been identified as a proton-sensing or extracellular pH-responsive G-protein-coupled receptor stimulating inositol phosphate production, reflecting the activation of phospholipase C. In the present study, we found that acidic pH stimulated cAMP accumulation, reflecting the activation of adenylyl cyclase, in addition to inositol phosphate production in OGR1-expressing cells. The cAMP response was hardly affected by the inhibition of phospholipase C. SPC inhibited the acidification-induced actions in a pH-dependent manner, while no OGR1-dependent agonistic action of SPC was observed. Thus, the dose-response curves of the proton-induced actions were shifted to the right in the presence of SPC regardless of stereoisoform. The antagonistic property was also observed for psychosine and glucosylsphingosine. In conclusion, OGR1 stimulation may lead to the activation of adenylyl cyclase in addition to phospholipase C in response to extracellular acidification but not to SPC. However, SPC and related lysolipids antagonize the proton-induced and OGR1-mediated actions. Keywords:: ovarian cancer G-protein-coupled receptor 1 (OGR1), sphingosylphosphorylcholine, psychosine, G-protein-coupled receptor, proton-sensing